Increasing hospital administrative efficiency via optimized office automation systems: A PDCA cycle approach - Ruiwen Lu; Yiming Zhang; Likang Luo; Quan Yuan; Shuihong Chen; Na Lv; Fenfang Zheng; Guofang Deng; Yuefeng Ma; Jie Xu; Zexin Chen; Fengjiang Zhang (PLoS ONE, 2025)
Background Increasing hospital administrative efficiency is crucial with regard to efforts to manage competitive pressures in healthcare. Despite extensive research on healthcare optimization, the role of Office Automation Systems (OASs) in administrative efficiency in the hospital context remains underexplored. This study addresses this gap by employing the plan–do–check–act (PDCA) cycle to improve administrative processes at the Second Affiliated Hospital, Zhejiang University School of Medicine. Methods As part of this study, the root causes of inefficiencies in administrative processes were analyzed, and a PDCA cycle approach was implemented to address these inefficiencies. Monthly training sessions were conducted, and rankings were displayed to raise awareness of this topic among employees. A total of 41 high-frequency processes were monitored and divided into the categories of medical research, clinical use, and daily administrative work. Data were collected from 2021 to 2023, and statistical analyses were conducted via SPSS and R software. Results Significant improvements in process implementation times were observed. With regard to clinical use processes, the median number of days required to process hospitalization and discharge procedures decreased from 4.33 in 2021 to 0.04 in 2023 (P < 0.001). Similarly, the number of days spent processing software requests decreased from 75.98 in 2021 to 31.33 in 2023 (P < 0.001). With respect to medical research processes, the median number of days required for animal laboratory access training applications decreased from 10.87 to 1.24 days (P < 0.01). Daily administrative processes also significantly improved, such that the median number of days spent on processing fixed asset disposal applications decreased from 5.96 to 4.21 (P < 0.01). Conclusion The application of the PDCA cycle significantly improved the efficiency of hospital administrative processes, thus highlighting the potential of this approach to serve as a valuable tool for continuous efforts to improve hospital administration. This study provides a framework for other hospitals seeking to increase their administrative efficiency via digital transformation and continuous quality improvement.